Diagnosing penetrating diaphragmatic injuries: CT scan is valuable but not reliable. Issue 1 (January 2022) - Cremonini, Camilla; Lewis, Meghan R.; Jakob, Dominik; Benjamin, Elizabeth R.; Chiarugi, Massimo; Demetriades, Demetrios
Highlights: Radiological diagnosis of uncomplicated diaphragmatic injuries is unreliable. Chest x-ray has a very limited role in the diagnosis of diaphragmatic injuries. Although CT scan can be helpful in the diagnosis of DI, it misses some injuries, with. potentially serious implications. Diagnostic laparoscopy remains an important tool for the evaluation of penetrating. Diaphragmatic injury. In the presence of diaphragmatic injury, clinicians should be aware of the risk for. tension pneumothorax upon insufflation for laparoscopy. Abstract: Background: The diagnosis of penetrating isolated diaphragmatic injuries can be challenging because they are usually asymptomatic. Diagnosis by chest X-ray (CXR) is unreliable, while CT scan is reported to be more valuable. This study evaluated the diagnostic ability of CXR and CT in patients with proven DI. Methods: Single center retrospective study (2009–2019), including all patients with penetrating diaphragmatic injuries (pDI) documented at laparotomy or laparoscopy with preoperative CXR and/or CT evaluation. Imaging findings included hemo/pneumothorax, hemoperitoneum, pneumoperitoneum, elevated diaphragm, definitive DI, diaphragmatic hernia, and associated abdominal injuries. Results: 230 patients were included, 62 (27%) of which had isolated pDI, while 168 (73%) had associated abdominal or chest trauma. Of the 221 patients with proven DI and preoperative CXR, the CXR showed hemo/pneumothorax in 99 (45%), elevated diaphragm in 51 (23%), and diaphragmatic hernia in 4 (1.8%). In 86 (39%) patients, the CXR was normal. In 126 patients with pDI and preoperative CT, imaging showed hemo/pneumothorax in 95 (75%), hemoperitoneum in 66 (52%), pneumoperitoneum in 35 (28%), definitive DI in 56 (44%), suspected DI in 26 (21%), and no abnormality in 3 (2%). Of the 57 patients with isolated pDI the CXR showed a hemo/pneumothorax in 24 (42%), elevated diaphragm in 14 (25%) and was normal in 24 (42%). Conclusions: Radiologic diagnosis of DI is unreliable. CT scan is much more sensitive than CXR. Laparoscopic evaluation should be considered liberally, irrespective of radiological findings.